Numerical analysis of non-isothermal walls driven-gas flow. (2018) - Hssikou, Mohamed; Baliti, Jamal; Alaoui, Mohammed
The gas flow driven by non-isothermal walls effect is studied by both macroscopic and kinetic approaches. In this study, the behaviour of a rarefied and Maxwell gas flow induced by the thermal creep and stresses within a two-dimensional microcavity is investigated using the direct simulation Monte Carlo (DSMC) method and the regularised 13-moment equations solution. The upper and bottom walls of the microcavity are linearly heated from the cold and environmental temperature T- to the hot one T+ . However, the left and right walls are kept at uniform and different temperatures T- and T+, respectively. The non-isothermal walls effect, at the vicinity of longitudinal walls, on the macroscopic gas properties is clarified for various values of the Knudsen number Kn, rarefaction degree. The agreement between DSMC and R13 results confirms the breakdowns of the classical Navier-Stokes and Fourier (NSF) theory for rarefied gas microflows.